Lived experiences of mothers with muscular dystrophy children, Kathmandu. - Prasai, Sangita (2012)
ABSTRACT: Muscular Dystrophy a genetic killer is a disorder with functional disability. This study was conducted with the purpose of exploring the lived experiences of mothers who are taking care of children with muscular dystrophy. Using a phenomenological design, nine mothers having Duchene Muscular Dystrophy children were selected. Data was gathered by using guidelines with In-depth interview method. Respondent's verbal as well as nonverbal clues were recorded by observation. Two to three in-depth interviews were carried out with each respondent along with audio tape recording and field notes. Official data were collected to give light to the findings of this study. Collected information was first transcribed from the verbatim then translated into English for reporting. Almost of the respondents perceived Duchene Muscular Dystrophy as a fatal form of neuromuscular disease which is progressive in nature and affects the muscle making the child unable to walk by 7-8 years of age. Treatment is expensive and complete treatment is not available till now. Majority of the respondents had suffered from psychosocial problems. However they were more concerned for the health and recovery of their child rather than their own health and difficulties. Their initial reaction to children's diagnosis was a feeling of mixed emotion. Majority of participants felt shocked and numb whereas others felt helpless. Most of them faced social problems due to their child's condition. They relieved their anxiety to some extent by sharing their feelings with others, assuring themselves and accepting their reality of their child's illness. Some had also adopted alternative therapy too. Thematic content analysis by Gibson (2006) was done to get the actual findings which were coded, categorized and organized into 4 clusters of themes: perception regarding disease, treatment modality, physical mobility of child, and coping mechanisms. Based on identified concepts, parents of DMD children are facing a huge array of problems which decrease the quality of life of parents. It is recommended to provide, social security, free supply of medicine, health facility and Palliative care for DMD child so that parents may face fewer problems.